2014
DOI: 10.1007/s10508-014-0349-4
|View full text |Cite
|
Sign up to set email alerts
|

Disgust and Sexual Arousal in Young Adult Men and Women

Abstract: Previous research suggested that disgust may interfere with healthy sexual functioning by demonstrating that women with sexual pain disorders are characterized by heightened disgust propensity, relatively strong (physiological and subjective) disgust responses when exposed to sexual stimuli, and relatively strong automatic sex-disgust memory associations. To broaden the understanding of the relationship between sex and disgust, Study 1 tested the relationship between trait disgust and sexual functioning in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Disgust may achieve this through multiple potential mechanisms in the current experiment. Similar to recent correlational findings (Grauvogl et al, 2014), disgust primes may have increased sexual arousal as the experiment progressed. While the initial effect of disgust on subjective sexual arousal may be inhibitory, disgust may subsequently increase sexual arousal as physiological responding to disgust cues increases.…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…Disgust may achieve this through multiple potential mechanisms in the current experiment. Similar to recent correlational findings (Grauvogl et al, 2014), disgust primes may have increased sexual arousal as the experiment progressed. While the initial effect of disgust on subjective sexual arousal may be inhibitory, disgust may subsequently increase sexual arousal as physiological responding to disgust cues increases.…”
Section: Methodssupporting
confidence: 85%
“…Some evidence also suggests a negative relation between sexual functioning and pathogen disgust propensity, but this evidence has almost exclusively examined the context of vaginal pain difficulties among women of predominately European descent (Borg et al, 2010; Borg et al, 2011). Similarly, recent evidence suggests disgust sensitivity and disgust propensity positively predict orgasm and sexual pain difficulties among women, but not men (Grauvogl et al, 2014). …”
Section: Disgust and Sex: Mutual Inhibitionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies have indicated an association between disgust and sexual arousal (de Jong et al, 2010; Stevenson et al, 2011; Borg and de Jong, 2012; Lee et al, 2014; Grauvogl et al, 2015). Among men, high levels of trait pathogen disgust sensitivity predicted higher levels of genital and subjective sexual arousal (Lee et al, 2014; Grauvogl et al, 2015). It seems that MSM individuals with high levels of pathogen disgust sensitivity are more likely to be sexually aroused and thus will have more casual sexual partners to release sexual arousal.…”
Section: Discussionmentioning
confidence: 93%
“…Second, our experimental setup did not allow us to use physiological methods to measure participants' level of sexual arousal. Instead, we relied on self-report measures that have been shown to only weakly (Chivers et al, 2010) or even negatively (Grauvogl et al, 2015) correlate with genital measures of sexual arousal, such as vaginal pulse amplitudes. In fact, self-reported sexual arousal may reflect more of a higher-order conscious appraisal of sexual cues, and therefore be more open to personal influences such as the cultural meaning of particular sexual cues, as compared to genital measurements that may represent faster and more unconscious information processing (Janssen, Everaerd, Spiering, & Janssen, 2000;Janssen, Prause, & Geer, 2007).…”
Section: Discussionmentioning
confidence: 99%